Pengaruh Media Video Terhadap Pengetahuan Dan Sikap Mengenai Perilaku Hidup Bersih Dan Sehat (PHBS) Tatanan Rumah Tangga Masyarakat Pesisir Di Dusun Lakatong Pulau Kabupaten Takalar - Zakiah; Septiyanti; Farihah Muhsanah (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2024)
Clean and Healthy Living Behavior (PHBS) is an important factor in preventing the spread of communicable and non-communicable diseases. Therefore, efforts to improve the level of public health in coastal areas can be done by educating housewives regarding the application of PHBS in the household environment. This research aims to provide education to housewives regarding household PHBS. The educational topics provided include the use of clean water, hand washing practices, healthy latrines, eradicating mosquito larvae, consuming fruit and vegetables, doing physical activity, as well as the dangers and impacts of smoking inside the house. The educational media used is material in the form of animated videos. This research design is quantitative using a Quasy-Experiment research design with NonEquivalent Control Group Design. The sample population in this study was all heads of families in Lakatong Island Hamlet with a sample size of 20 families in the experimental group and 20 families in the control group. The results of this research show that there is an influence of video media regarding household PHBS after intervention through video media, namely a value of p = 0.000 < 0.05. The Mangarabombang Community Health Center needs to increase education regarding PHBS in household arrangements, both through posyandu, women's social gatherings and other activities.